ANALISA STRUKTUR KOLOM PADA PROYEK PEMBANGUNAN GEDUNG RAWAT JALAN DAN BASSEMENT RSUD MAJALENGKA - Indra Lesmana, Dani; Rijaluddin, Arief (Universitas Majalengka, 2021)
ABSTRACT Majalengka Regency is an area in West Java Province that is developing with various developments in all fields to create a more advanced citizen of Majalengka Regency. existing health facilities no longer meet overall health needs. The construction of the Outpatient Building and Bassement of the Majalengka Hospital is one of the efforts of the Majalengka district government to improve health services, this development is motivated by limited facilities, in this case the outpatient building in Majalengka Hospital which is currently running. Design of reinforced concrete column used a thickness of 550 mm with a concrete quality of 〖f '〗 _ c 25 Mpa and steel quality 〖f'〗 _ y 240 Mpa. Longitudinal reinforcement uses steel reinforcement as much as 16 with a diameter of 25 mm and stirrups using steel with a diameter of 13 mm with a distance of 150 mm for the top stirrup and 100 mm for the bottom stirrup. The results of the analysis of the column structure based on strength and deformation with the calculated results from the SAP 2000 v.14 program obtained shear (Vu) 43.03 KNm and axial force (Pu) 38.644 KNm and reaction moment (M) 60.3748 KNm. The output results from SAP are then processed by checking the column calculation manually P_ (n max) ˃ Pu so that the value obtained is 4235562.5 Kn> 38.644 Kn where the axial load (Pu) cannot exceed the compressive strength of the plan (〖∅P〗 _ (n max)) SNI 03-2847-2002 Article 12.3.6. In determining the shear reinforcement, the calculation result is 763.8 mm with the stirrup distance (s) is 347,381 mm where s <600.